CCNA routing and switching review guide - Lammle, Todd (J. Wiley & Sons, 2014)
Todd Lammle's focused, concise review guide, updated for the latest CCNA exams CCNA is one of the most sought after certifications for IT professionals. If you're preparing for the CCNA Routing and Switching certification, this Sybex review guide offers the best quick review available. Organized by exam objective, it's the perfect supplement to other learning tools, including the Sybex CCNA Routing and Switching Study Guide(ISBN: 9781118749616). All exam topics from exams 100-101, 200-101, and 200-120 are thoroughly covered, and additional study materials including bonus exams, electronic flashcards, and a searchable glossary of terms are also available.-Organized by exam objectives, this Sybex review guide provides a thorough and intensive review of all topics required for the CCNA Routing and Switching certification exams -Lead author Todd Lammle is a Cisco networking authority and the bestselling author of numerous Cisco exam-prep books -Covers exams 100-101, 200-101, and 200-120, and is a perfect companion to Sybex's CCNA Routing and Switching Study Guide -Additional study materials are available, including bonus practice exams, electronic flashcard questions, and a glossary of terms in searchable PDF form Using the CCNA Routing and Switching Review Guide will boost your confidence as you approach exams 100-101, 200-101, and 200-120.